Otentisitas Konsep al-Murâbahah Di Bank Syariah - Suprihatin Suprihatin (AHKAM : Jurnal Ilmu Syariah, 2015)
The aim of this research is  to  returning the authenticity of al-murâbahah in syariah bank. The method of this research is qualitative library method with symbolism  interaction approach.   The  problem of  this research is an unauthenticity of al-murâbahah in syariah bank  because  there is no trading. Al-murâbahah in syariah bank was  operated  base on funding. So that  al-murâbahah in syariah bank can be called unauthentic. The urgency to returning the authenticity of al-murâbahah is to obey the syariah,  to make someone who operated al-murâbahah in syariah bank did’n have a split of thinking,  to built a correspondence thruth and coherence thruth in  Islamic civilization.DOI: 10.15408/ajis.v15i1.2850